2012
DOI: 10.1007/s00339-012-7279-6
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and characterization of lines printed through laser-induced forward transfer

Abstract: The possibility of printing two-dimensional micro patterns of biomolecule solutions is of great interest in many fields of research in biomedicine, from cell-growth and development studies, to the investigation of the mechanisms of communication between cells. Although laser-induced forward transfer (LIFT) has been extensively used to print micrometric droplets of biological solutions, the fabrication of complex patterns depends on the feasibility of the technique to print micron-sized lines of aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…The actual thickness values that correspond to "thicker" or "thinner" are dependent on voxel size and are listed below each SEM image. made by linking multiple voxels in a chain have been demonstrated, although low viscosity inks were generally needed to achieve line widths below 250 m [19]. The primary obstacle to overcome in this case is the quality of the interface between multiple voxels, as this limits the overall electrical conductivity of the chain.…”
Section: Fabrication and Characterization Of Cpwsmentioning
confidence: 97%
See 1 more Smart Citation
“…The actual thickness values that correspond to "thicker" or "thinner" are dependent on voxel size and are listed below each SEM image. made by linking multiple voxels in a chain have been demonstrated, although low viscosity inks were generally needed to achieve line widths below 250 m [19]. The primary obstacle to overcome in this case is the quality of the interface between multiple voxels, as this limits the overall electrical conductivity of the chain.…”
Section: Fabrication and Characterization Of Cpwsmentioning
confidence: 97%
“…Overall, we found that the double layer geometry was the most reliable, with 12 out of 12 1-mm long chains surviving the curing stage, whereas only 6 of 12 1-mm long chains possessing the single layer geometry survived. Chains fabricated by either method possessed a relatively consistent width throughout the entire length of the chain regardless of the stacking geometry, which has proven to be a challenge for low viscosity inks [19,20]. Single-layer and double-layer chains were measured to have an effective resistivity of ∼7.5 × 10 −8 m and ∼9 × 10 −8 m, respectively, roughly 5-6 times the value of bulk silver (1.6 × 10 −8 m) and comparable to the resistivity values quoted by the Ag paste manufacturer, ∼3 × 10 −8 m. [21] As an aside, we refer to this value as "effective resistivity" because it includes the interfacial resistance between voxels, which is a geometric factor and is not intrinsic to the material.…”
Section: Fabrication and Characterization Of Cpwsmentioning
confidence: 99%
“…Although the experimental conditions not being exactly the same as those in ref. (Palla-Papavlu et al, 2013), it can assumed that the dynamics taking place are essentially the same as those described in ref. (Palla-Papavlu et al, 2013).…”
Section: Obp Deposition By Liftmentioning
confidence: 99%
“…(Palla-Papavlu et al, 2013). Printing of uniform continuous lines by LIFT and covering the entire active area of the SAW resonator can be explained in terms of the dynamics of needle-like jets which propagate along a gap between donor and receiver substrate (Duocastella et al, 2010;Palla-Papavlu et al, 2013).…”
Section: Obp Deposition By Liftmentioning
confidence: 99%
“…The LIFT of nanoparticle inks on the other hand constitutes a more conventional approach, probably closer to the current industrial demands. However, it is not free from problems either: it is in general difficult to find the right process parameters to obtain stable continuous lines free from bulging [18][19][20][21]. This problem is not specific from LIFT, but also common to other even more conventional techniques, such as inkjet printing, for instance.…”
Section: Introductionmentioning
confidence: 95%